The end of slavery in Africa and the Americas: a comparative approach - Schmieder, Ulrike (Sklaverei und Postemanzipation, 2011)
The Atlantic slave trade and a very small place in Africa : global processes and local factors in the history of Little Popo, 1680s to 1860s / by Silke Stickrodt -- The hobgoblins of the Middle Passage : the Cape and the trans-atlantic slave trade / by Patrick Harries -- The names of slavery and beyond : the Atlantic, the Americas and Cuba / by Michael Zeuske -- The Moravian mission and the emancipation of slaves in the Caribbean / by Claus Füllberg-Stolberg -- Black politics in free Jamaica, 1838-1865 / by Swithin R. Wilmot -- Slavery, abolition and post-emancipation in the French and Spanish Caribbean, especially Martinique and Cuba, in the network of global relations / by Ulrike Schmieder -- The end of slavery, the role of the Freedmen's Bureau and the introduction of peonage / by Norbert Finzsch -- Afterword : trajectories of change / by Jan-Georg Deutsch